Exploring the influence of urban art interventions on attraction and wellbeing: an empirical field experiment - Dehove, Margot; Mikuni, Jan; Podolin, Nikita; Moser, Martin Karl; Resch, Bernd; Doerrzapf, Linda; Boehm, Pia Marlena; Prager, Katharina; Leder, Helmut; Oberzaucher, Elisabeth (Frontiers in Psychology, 2024)
While cities are attractive places, brimming with opportunities and possibilities for their inhabitants, they have also been found to have negative consequences, especially on physical and mental health. In a world of ever-growing urban populations, it is important to understand how to make cities healthier and more pleasant places to live. In the present study, we investigated the impact of art as an urban intervention and compared this to the well-known effects of greenery (i.e., plants and vegetation) in an identically framed intervention. Specifically, we looked at how people engage with a Graetzloase (a type of parklet) and its embedding urban environment, in terms of visual and spatial attraction as well as wellbeing. The Graetzloase displayed either abstract art or greenery and was placed on two distinct streets that, among other elements, also contained art and greenery. Our field study captured the ongoing experiences during people’s exploration of the urban environment by employing mobile eye-trackers and physiological devices. While our findings demonstrated a certain level of visual and spatial attraction towards the Graetzloases, it was not as pronounced as initially anticipated. Nevertheless, our analyses still inform on What decorating element should be placed in a Graetzloase, as well as Where to implement the Graetzloase. Our results suggest that artistic elements are more visually attractive (i.e., they were looked at for longer times) than the green, and that both visual and spatial attraction toward the Graetzloases are greatly impacted by the street context. We found that the artistic Graetzloase when displayed in a wide street containing green elements, is visually more present in the participant visual field than all the other experimental combinations. The more precise analyses of the participant viewing behaviour confirm this trend. Regarding the wellbeing, we found no evidence for the impact of street context or the types of decorations in the Graetzloases. Our results establish an initial empirical foundation for the design and placement of, not only future parklets but also urban art interventions in general.